ANALISIS KEMAMPUAN PEMANFAATAN MODAL USAHATANI KACANG TANAH DI DESA TOMBASIAN ATAS KABUPATEN MINAHASA MENGGUNAKAN RASIO NET PROFIT MARGIN DAN RETURN ON INVESTMENT (Utilization Capability Analysis of Peanut Business Capital in Tombasian Village of Minahasa Regency Using Net Profit Margin and Return On Investment Ratio) - Hetmi Rafika Mamoto; Eyverson Ruauw; Theodora M. Katiandagho (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
The purpose of this study was to determine the source of financing, the amount of capital needed, and the capital ability to generate profits in peanut farming in Tombasian Atas Village, Minahasa Regency. The sample used in this study consisted of 10 peanut farmers. The method used was descriptive quantitativeÂ and the analysis techniques of Net Profit Margin (NPM) and Return On Investment (ROI).The results showed that for the source of capital from the respondents, 60% came from their own capital and as much as 40% came from loans through People's Business Credit (KUR). The amount of peanut farming capital in one growing season varied from Rp. 3,373,333 to Rp. 9,115,000 which was influenced by the area of land and the financing policy of each respondent. In general, the ability to use capital in generating profits from peanut farming by farmers could be stated as â€œgoodâ€ because the Net Profit Margin (NPM) was 43% on average and Return on Investment (ROI) was 81% on average. Therefore, peanut farmers in Tombasian Atas Satu Village, Minahasa Regency are advised to continue developing peanut farming.